Antarctic Geological 1: 250,000 map series - Mount Joyce Quadrangle (Victoria Land) - BARONI, CARLO; MUSUMECI, GIOVANNI; CAPPONI G; CRISPINI L; MECCHERI M; PERTUSATI P. C. (Museo Nazionale dell'Antartide, 2002)
Geological map of Mt. Joyce Quadrangle. Research conducted in the framework of the Italian National Antarctic Programme (PNRA).